The Impact of Quality and Price on Purchase Decisions Mediated by Customer Satisfaction - Reva, Yayu Nova; Putri, Ivana Nabila; Andita, Khalisa Putri; Zalzabyella, Arzella; Purwanto, Edi (Journal of Business & Applied Management, 2024)
This study investigates the influence of product quality and price on purchase decisions, with customer satisfaction as a mediating factor, focusing on Samsung smartphone users in Indonesia. Utilizing a quantitative approach, the research examines the causal relationships among variables, employing Structural Equation Modeling-Partial Least Squares (SEM-PLS) for analysis. Data were collected through a structured online questionnaire targeting 113 respondents using convenience sampling. The findings reveal that product quality significantly impacts customer satisfaction and directly influences purchase decisions, highlighting its pivotal role. Price also positively affects customer satisfaction but shows minimal direct influence on purchase decisions, underscoring the mediating role of satisfaction. Customer satisfaction strongly drives purchase decisions as a crucial intermediary between independent and dependent variables. These insights emphasize the necessity for businesses to prioritize product quality and strategies that enhance customer satisfaction to remain competitive in the smartphone industry.